Gas Responsive Nanoswitch: Copper Oxide Composite for Highly Selective H2S Detection. (16th August 2019) - Paul, Andrej; Schwind, Bertram; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten
Abstract: A nanocomposite material based on copper(II) oxide (CuO) and its utilization as a highly selective and stable gas‐responsive electrical switch for hydrogen sulphide (H2 S) detection is presented. The material can be applied as a sensitive layer for H2 S monitoring, e.g., in biogas gas plants. CuO nanoparticles are embedded in a rigid, nanoporous silica (SiO2 ) matrix to form an electrical percolating network of low conducting CuO and, upon exposure to H2 S, highly conducting copper(II) sulphide (CuS) particles. By steric hindrance due to the silica pore walls, the structure of the network is maintained even though the reversible reaction of CuO to CuS is accompanied by significant volume expansion. The conducting state of the percolating network can be controlled by a variety of parameters, such as temperature, electrode layout, and network topology of the porous silica matrix. The latter means that this new type of sensing material has a structure‐encoded detection limit for H2 S, which offers new application opportunities. The fabrication process of the mesoporous CuO@SiO2 composite as well as the sensor design and characteristics are described in detail. In addition, theoretical modeling of the percolation effect by Monte‐Carlo simulations yields deeper insight into the underlying percolation mechanism and the observed response characteristics. Abstract : Stabilization of the copper oxide (CuO)–copper sulphide (CuS) electrical percolation transition is achieved by morphological stabilization utilizing porous silica. The network of low conducting CuO and, upon exposure to hydrogen sulphide (H2 S), highly conducting CuS particles exhibits a switching type conductance change correlated to H2 S uptake. The material can be applied as a robust H2 S sensor in natural gas plants.